Pengaruh Mekanisme Tata Kelola Perusahaan Terhadap Penghindaran Pajak: Studi Pada Perusahaan Sektor Consumer Cyclicals Yang Terdaftar Di Bursa Efek Indonesia - Sianturi, Dame; Wahyudi, Ilham; Hernando, Riski (Jurnal Akuntansi & Keuangan Unja, 2025)
The purpose of this study is to detemine the effect of good corporate governance mechanisms on tax avoidance in consumer cyclicals sector companies listed on the indonesia stock exchange (IDX) in 2021-2023. This study is quantitative and employs a documentation methode. The study population comprised 164 companies. The sample selection methode used purposive sampling, resulting in 49 companies, with a total sample size of 147 meeting the criteria. The data used were secondary data  from company annual reports, and documentation was used as the data collection methode. The data analysis techniques used were descriptive statistics and multiple linear regression analysis using SPSS version 27 software. The results of this study revealed that the variables of managerial ownership, institutional ownership, independent board of commissioners, and audit committee, have a significant effect on detecting tax avoidance, and managerial ownership, institutional ownership, independent board of commissioners, and audit committee have simultaneous effect